SUBACUTE MASSIVE PULMONARY THROMBOEMBOLISM IN YOUNG PATIENTS: A COMPARATIVE PRESENTATION - Gujaničić, Dušica; Benović , Nataša; Nešović , Stefan (Sanamed, 2024)
Introduction: Subacute massive pulmonary embolism is a potentially fatal condition that can manifest in various clinical ways in a young patient, from mild and nonspecific to lethal. The incidence of pulmonary embolism in the younger population should not be overlooked, whether it involves individuals with certain risk factors, either genetic or acquired, or individuals with unidentified risk factors. Case Presentation: We are presenting two young patients, aged 35 and 37, who had a protracted course of disease and clinical manifestations at least 15 days before admission. The first patient had nonspecific pains and sensations in the chest area and coughed up blood on two occasions. The day before admission, he had an intense one-hour swimming workout. The second patient had rapid fatigue and choking, which led to an echocardiogram of the heart and a treadmill test that was terminated at the second level due to poor condition, as stated by the patient himself. He came in due to intense pain in the epigastrium, preceded by a loss of consciousness. In both patients, a diagnosis of massive PTE was made: the first by Multi-Slice Computed Tomography of the pulmonary artery (MSCTPA) and the second by clinical autopsy. The first patient received thrombolytic therapy and was discharged with NOACs (Apixaban) after 10 days of hospitalization. Conclusion: It is always necessary to keep in mind the possibility of PTE, even in younger patients and in cases with subtle clinical presentations, even without identified predisposing factors.